2006
DOI: 10.1093/tropej/fml080
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Care Practices at Home: Effect of a Hospital-based Intervention in Sri Lanka

Abstract: The aim of the present study was to evaluate the effect of an essential newborn care (ENC) training programme for maternity ward staff in improving newborn care practices after hospital discharge. A before-and-after study was conducted in the community involving mothers who had given birth in two hospitals in the Puttalam district in Sri Lanka. The intervention was a 4-day training programme and primarily aimed at increasing knowledge and skills of ENC among health care providers in the maternity units of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…3 Visits on subsequent of health workers in postnatal home visits. 18 The odds of practising safe breastfeeding among mothers was found to be higher (odds ratio: 7.6; 95% confidence interval: 6.03-9.71) among those who received one-on-one counselling and hands-on support in an intervention trial where community-based trained workers made home visits within the first three days of birth in Bangladesh. 19 Therefore, more intensive counselling by ASHAs in the first three postnatal visits might further improve adoption of this practice.…”
Section: Discussionmentioning
confidence: 95%
“…3 Visits on subsequent of health workers in postnatal home visits. 18 The odds of practising safe breastfeeding among mothers was found to be higher (odds ratio: 7.6; 95% confidence interval: 6.03-9.71) among those who received one-on-one counselling and hands-on support in an intervention trial where community-based trained workers made home visits within the first three days of birth in Bangladesh. 19 Therefore, more intensive counselling by ASHAs in the first three postnatal visits might further improve adoption of this practice.…”
Section: Discussionmentioning
confidence: 95%
“…Training doctors, nurses, and midwives in community hospitals in Sri Lanka in the Essential Newborn Care course reported improved care practices in a group of 1186 newborns but major outcomes were not reported. 28,29 We recently reported that the current Essential Newborn Care course reduced all-cause 7-day and perinatal mortality in low-risk health care urban health clinics in Zambia. 12 Evaluations of other neonatal care packages have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The only clinical studies on the effect of ENC training reported increased use of many of the practices taught. 13,14 Mortality rates and other major outcomes were not assessed because the studies were too small to detect an effect. The ENC course improved the knowledge and skills of midwives in Zambia.…”
Section: Figurementioning
confidence: 99%
“…The ENC course complements Pregnancy, Childbirth, Postpartum and Newborn Care: A Guide for Essential Practice, 10 and together the course and the guide provide evidence-based guidelines for routine care and initial treatment of neonates during the first week after birth. The ENC course has been taught, [11][12][13][14] but its effect on major outcomes has not been tested in a large clinical study. The Neonatal Resuscitation Program (NRP) of the American Academy of Pediatrics is a train-thetrainer, hands-on course to develop expertise in the evidenced-based knowledge and skills of neonatal resuscitation.…”
mentioning
confidence: 99%